Aluminum Matrix Composites Manufactured using Nitridation-Induced Self-Forming Process - Lee, Kon-Bae (Sci Rep, 2019)
Conventional manufacturing processes for aluminum matrix composites (AMCs) involve complex procedures that require unique equipment and skills at each stage. This increases the process costs and limits the scope of potential applications. In this study, a simple and facile route for AMC manufacturing is developed, a mixture of Al powder and the ceramic reinforcement is simply heated under nitrogen atmosphere to produce the composite. During heating under nitrogen atmosphere, the surface modification of both Al and the reinforcement is induced by nitridation. When the oxide layer covering Al powder surface is transformed to nitrides, temperature in the local region increases rapidly, resulting in a partial melt of Al powder. The molten Al infiltrates into the empty space among Al powder and reinforcement, thereby enabling consolidation of powders without external forces. It is possible to fabricate AMCs with various types, sizes, volume fractions, and morphologies of the reinforcement. Furthermore, the manufacturing temperature can be lowered below the melting point of Al (or the solidus temperature for alloys) because of the exothermic nature of the nitridation, which prevents formation of un-wanted reactants. The relative simplicity of this process will not only provide sufficient price competitiveness for the final products but also contribute to the expansion of the application scope of AMCs.